Advanced parallel processing technologies : 11th International Symposium, APPT 2015, Jinan, China, August 20-21, 2015, Proceedings /: 11th International Symposium, APPT 2015, Jinan, China, August 20-21, 2015, Proceedings. (2015) - Unknown
No abstract available